Transparência subnacional: um estudo das variáveis determinantes para o atendimento da Lei de acesso à informação nos municípios brasileiros - Arruda, Carlos Eduardo Girão de (2016)
The strengthening of democracy requires access to information. This has been regulated by legal frameworks over the past decades. However we know that the practice sometimes does not match the theory. Check how municipalities are implementing their obligations in the face of LAI passes, in addition to assessing compliance by investigating the causes of any gaps in such care. More than that, try to identify variables that impact more decisively such implementation. From this premise, we seek to identify these factors and quantify the impact of each on the result of evaluation of the transparency indexes created recently - the Brazil Transparent Scale (EBT). He fulfilled this task by means of the following: (i) carrying out bibliographic research from the academic production; (ii) cataloging and analysis of the legal instruments for transparency; (iii) survey of the determinants for transparency; (iv) establishing the relationship between these variables and the transparency index found by means of statistical techniques, especially correlation and regression. The surveys found that the academic production of the Public Administration area on the subject is still lacking and that the transparency of causality research is needed; that given the correlation between the selected variables and transparency, the findings are a promising hypotheses that deserve more detailed study, with qualitative techniques to a more accurate determination of cause and effect.